PENGEMBANGAN MEDIA E-KOMIK BERBASIS CANVA TERINTEGRASI PROBLEM BASED LEARNING (PBL) PADA PEMBEJALARAN IPAS DI KELAS V SEKOLAH DASAR - Annefa, Putri Salda; Arwin; Hamimah; Gita Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was driven by low student interest and understanding of abstract Science and Social Studies (IPAS) materials, alongside limited innovative digital learning media in elementary schools. Conventional teacher-centered learning often leaves students struggling to analyze contextual problems. This study aims to develop Canva-based e-comic media integrated with the Problem-Based Learning (PBL) model on the topic